A SEMIOTIC ANALYSIS: REFLECTION OF ETHICAL AND PSYCHOLOGICAL HEDONISM IN JANE AUSTEN’S NOVEL “EMMA” - Nuryuliana, Nuryuliana; Nur, Riola Haya (ELITERATE : Journal of English Linguistics and Literature Studies, 2022)
This dissertation examines hedonism in 'Jane Austen's Novel Emma. The aims are to ascertain the hedonism, the varieties of hedonism, expressed by the novel's protagonist that the researcher want to impart to the readers. The study included qualitative research methods. The data for this study were derived from the "Jane Austen Novel Emma." Then, secondary data were gathered through a literature review and other sources of information relevant to the research's objective. After examining the work, it was discovered that there are two types of hedonism: (1) ethical hedonism, which occurs in 17 instances, and (2) psychological hedonism, which occurs in 8 instances. Additionally, the research found that the protagonist embodies hedonistic evidences on three levels: representation, ideology, and actuality. The criterion for hedonism in the protagonist is anything, including physical appearance, wealth, consumption, environment, characters, conflict, and story, as well as race, class, and materialism. In other words, happiness is synonymous with pleasure. According to the results above, readers can learn and expand their understanding of all facets of hedonism and the various forms of hedonism in the novel. Additionally, this study is beneficial in teaching learning processes such as using literature as a reference to gather knowledge about the novel and its aspects.